2008
DOI: 10.1523/jneurosci.1952-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and Inhibition Jointly Regulate Cortical Reorganization in Adult Rats

Abstract: The primary somatosensory cortex (SI) retains its capability for cortical reorganization after injury or differential use into adulthood. The plastic response of SI cells to peripheral stimulation is characterized by extension of cortical representations accompanied by changes of the receptive field size of neurons. We used intracortical microstimulation that is known to enforce local, intracortical synchronous activity, to induce cortical reorganization and applied immunohistochemical methods in the same indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 77 publications
4
37
0
Order By: Relevance
“…Cortical application of bicuculline has allowed us to demonstrate that GABAergic transmission is critically placed to maintain the form of cortical motor representations (Jacobs and Donoghue, 1991;Benali et al, 2008) and to modulate the functional link between cortical points (Schneider et al 2002). In the present study, cortical application of bicuculline at a subconvulsive concentration (Stojic et al, 2000) resulted in global increase of M1 excitability.…”
Section: Neurobiological Mechanisms Underlying M1 Changesmentioning
confidence: 52%
“…Cortical application of bicuculline has allowed us to demonstrate that GABAergic transmission is critically placed to maintain the form of cortical motor representations (Jacobs and Donoghue, 1991;Benali et al, 2008) and to modulate the functional link between cortical points (Schneider et al 2002). In the present study, cortical application of bicuculline at a subconvulsive concentration (Stojic et al, 2000) resulted in global increase of M1 excitability.…”
Section: Neurobiological Mechanisms Underlying M1 Changesmentioning
confidence: 52%
“…However, more chronic effects on cell function were not determined, and it remains possible that alterations in the balance of excitation and inhibition conjointly regulate the cortical map in a particular spatial arrangement, in a manner similar to that observed after cortical plasticity induced by intracortical microstimulation. 46 In this interpretation, enhanced c-Fos cell activity that we observed after cABC infusion would occur in glutamatergic neurones, limited by inhibitory zones of increased cell numbers containing GABA. This would seem to concur with previous in vitro work showing increased L-glutamate trafficking and plasticity at synapses after digestion of the surrounding PNNs.…”
Section: And (E) Gap43mentioning
confidence: 68%
“…This finding was surprising, as H 3 antagonists including GSK189254 are known to activate the intermediate early gene c-fos in both the prefrontal and somatosensory cortex Southam et al, 2009), and cortical reorganization of sensory information is accompanied by increased glutamatergic drive and c-fos activation (Benali et al, 2008). In contrast, chronic treatment (40 days) with the 5-HT 6 receptor antagonists SB-271046 and SB-399885 markedly increase NCAM PSA expression in the entorhinal and perirhinal cortex , an effect that may relate to their ability to increase glutamate outflow (Dawson et al, 2001), as a similar action is not observed with GSK189254 (Medhurst et al, 2007).…”
Section: Discussionmentioning
confidence: 99%